From acute pulmonary embolism to post-pulmonary embolism sequelae: functional and hemodynamic implications - Farmakis, Ioannis T.; Keller, Karsten; Barco, Stefano; Konstantinides, Stavros; Hobohm, Lukas (Vasa, 2023)
Summary: Aim of this narrative review is to summarize the functional and hemodynamic implications of acute PE and PE sequelae, namely the post-PE syndrome. Briefly, we will first describe the epidemiology, diagnostic procedures, and therapeutic approaches of acute PE. Then, we will provide a definition of the post-PE syndrome and present the so far accumulated evidence regarding its epidemiology and the implications that arise for further diagnosis and treatment. Lastly, we will explore the most devastating long-term complication of PE, namely chronic thromboembolic pulmonary hypertension (CTEPH), and recent advances in its management.